Inpatient Service Efficiency Analysis Based On Inpatient Indicators (BOR, ALOS, TOI and BTO) (Study on Inpatient Indicators at Gondanglegi Islamic Hospital, Malang, Indonesia): Suhartinah*, Muhammad Arief Rachman, Muhammad Masyhur, Asrianni Rindha Wahyuningsih (JOURNAL OF MEDICAL RECORDS AND HEALTH INFORMATION, 2020)
Statistics are a description of a condition poured down in numbers and can be taken from reports, research or medical record sources. Statistics can be used to calculate various indicators one of which is an inpatient indicator. These indicators are BOR (Bed Occupancy Rate), ALOS (Average Lenght Of Stay), TOI (Turn Over Interval) and BTO (Bed Turn Over). The inpatient indicator can be presented in a Barber-Johnson chart showing the point to be in an efficient area or outside. This research uses quantitative method with descriptive approach. Because this research describes and presents systematically data in Gondanglegi Islamic Hospital. Based on collecting data, the data will be applied in the Barber-Johnson formula and in the figure on the Barber-Johnson chart. The result of the calculation of the inpatient indicator at Gondanglegi Islam Hospital in January 2017 obtained BOR value of 38.46%; ALOS of 2.55 days; TOI of 4.1 days and BTO of 4.7 times. Then in February 2017 obtained a BOR value of 43.29%; ALOS of 2.75 days; TOI of 3.6 days and BTO of 4.4 times. And in March 2017 obtained BOR value of 44.44%; AVLOS of 2.87%; TOI of 3.6 days and BTO of 4.8 times. the result of the calculation of the points or lines of the inpatient indicator on the Barber-Johnson chart are outside the efficient area. Based on Barber-Johnson's efficiency standards indicates that Gondanglegi Islamic Hospital has not met the predetermined efficiency standards because the Barber-Johnson chart shows that the indicator's points and lines are outside the efficient area. Keyword : Efficiency, Indicators of Inpatient, Barber-Johnson.